2016
DOI: 10.1007/s13277-016-4912-6
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol inhibits cell proliferation and glycolysis in esophagus squamous cell carcinoma via targeting EGFR signaling pathway

Abstract: Antitumor activity of kaempferol has been studied in various tumor types, but its potency in esophagus squamous cell carcinoma is rarely known. Here, we reported the activity of kaempferol against esophagus squamous cell carcinoma as well as its antitumor mechanisms. Results of cell proliferation and colony formation assay showed that kaempferol substantially inhibited tumor cell proliferation and clone formation in vitro. Flow cytometric analysis demonstrated that tumor cells were induced G0/G1 phase arrest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…4). Furthermore, results of these studies demonstrate that KMFdependent arrest of G0/G1 or G2/M transition is possibly due to inhibition of epidermal growth factor receptor (EGFR) activity, hexokinase-2 expression (Yao et al, 2016), inhibition of the activity of estrogen (Kim et al, 2016) or uptake of glucose (Azevedo et al, 2015). Of note, growth factors, hormones, glucose and hexokinases are positive regulators of cell cycle.…”
Section: Cell Cycle Arrest and Apoptosis By Kaempferolmentioning
confidence: 96%
See 2 more Smart Citations
“…4). Furthermore, results of these studies demonstrate that KMFdependent arrest of G0/G1 or G2/M transition is possibly due to inhibition of epidermal growth factor receptor (EGFR) activity, hexokinase-2 expression (Yao et al, 2016), inhibition of the activity of estrogen (Kim et al, 2016) or uptake of glucose (Azevedo et al, 2015). Of note, growth factors, hormones, glucose and hexokinases are positive regulators of cell cycle.…”
Section: Cell Cycle Arrest and Apoptosis By Kaempferolmentioning
confidence: 96%
“…Recent in vitro and in vivo studies have shown the antiproliferative and proapoptotic activities of KMF against various types of cancers including breast (Azevedo et al, 2015;Kim, Hwang, & Choi, 2016;Liao et al, 2016), ovarian (Luo, Rankin, Li, Depriest, & Chen, 2011), lung (Kuo et al, 2015), pancreas (Zhang, Chen, Li, Chen, & Yao, 2008), esophagus (Yao et al, 2016), stomach , colon , prostate (Halimah et al, 2015), bladder (Dang et al, 2015), kidney (Song et al, 2014) and others. Most of these studies demonstrate that the mechanism of KMF is dependent on the inhibition of proliferation of various cancer cells either via cell cycle arrest or induction of apoptosis (Kuo et al, 2015;Liao et al, 2016).…”
Section: Cell Cycle Arrest and Apoptosis By Kaempferolmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaempferol ( Figure 1 ) is a flavonoid abundantly found in Psidium guajava , ginger, propolis and teas [ 3 , 4 , 5 ]. The anti-inflammation and anti-diabetic activity of kaempferol has gained much attention [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…HK-2 is considered to be the principal regulated isoform in different cell types [ 6 ]. The analysis of clinical specimens demonstrated that HK2 overexpression occurs in a variety of cancers, including breast cancer [ 7 ], gastric cancer [ 8 ], esophageal carcinoma [ 9 ], and cervical cancer [ 10 ]. In HCC, HK-2 was found to be overexpressed in 55.67% of clinical specimens and was closely correlated with the poor survival of patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%